Head-to-head opponent mitigates mental fatigue effects during a 20-km time trial in well-trained cyclists - Ferreira, M. E. C.; Carmo, E. C.; Frota-Júnior, L. S.; de Sousa Fortes, L. (Scandinavian Journal of Medicine & Science in Sports, 2023)
We aimed to analyze the effect of a head-to-head virtual race on 20-km time trial performance in well-trained mentally fatigued cyclists. A total of 24 male professional cyclists participated in the present study, which was conducted in a within-factors design [four experimental conditions × four times (throughout 20-km time trial cycling)]. An avatar representing the participant on the racecourse was visible during the time trials. Then, a second virtual avatar representing the opponent was projected onto the screen in the mental fatigue head-to-head and control head-to-head experimental conditions. Measurements [rating of perceived exertion, heart rate, and eye-tracking measures (i.e., pupil diameter)] were performed every 5-km throughout the 20-km time trial. As a result, impaired total time, power output, and cadence throughout the 20-km cycling time trial were found for mental fatigue compared to mental fatigue head-to-head, control head-to-head, and control conditions (p < 0.05). Also, impaired 20-km time trial performance (total time, power output, and cadence) was found for mental fatigue head-to-head compared to control head-to-head (p < 0.05). Moreover, lower RPE was found for the control and control head-to-head conditions than mental fatigue head-to-head and mental fatigue experimental conditions (p < 0.05). Higher pupil diameter was also found for mental fatigue head-to-head, control head-to-head, and control than the mental fatigue experimental condition (p < 0.05). In summary, the overall performance throughout the 20-km cycling time trial was improved by the presence of a virtual opponent for the mentally fatigued cyclists.